Customer relationship management and satisfaction levels in banking industry / Abdul Razak Kamaruddin, Safiek Mokhlis and Norliza Muhamed - Kamaruddin, Abdul Razak; Mokhlis, Safiek; Muhamed, Norliza (2002)
Customer relationship management (CRM) is critical to corporate success and managing customer relationships have become extremely important in achieving customer satisfaction. Therefore, in order to achieve high customer satisfaction, companies must learn the skills of how to deliver effective services to their customers. This paper examined the dimensions of customer service viz., service strategy, service environment and service delivery towards the implementation customer relationship management in the banking sector. It also provides some explanations on how CRM can influence the satisfaction of bank's customers. Questionnaires were distributed and completed by a sample of 280 university students in Terengganu. Self-administered survey method was employed to solicit the required information. The data were then analyzed using the SPSS computer program. The findings showed some significant relationships between service delivery and CRM. Similarly, there is a meaningful explanation between CRM and customer satisfaction. Against the backdrop of customer relationship management, it is suggested that bank management should be more attentive in improving the service strategy aspects such as reliability, accessibility, courtesy, communication, empathy and responsiveness.